Communication by training specialists of the distance form of education - Oleksenko, V. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The aim of the article is to show how to realize communication by different forms of organizing the learning process and the ways of upbrining students by means of distance education. Our research shows that if communication is directed not only to the control of students’ knowledge and skills but also to the diagnostics of their activity, then it provides differentiated approach, captivates a student with a thought about his prospect, stimulates to working on his own with the purpose of improving his professional abilities. Information of an up-bringing nature under a separate rubric, the workedout tutor’s exercise-book are a pearl of communications that is described in the article.